Sidney Morris Davis memoirs - Davis, Sidney Morris, -1899.
Holograph manuscript by Davis recounting his Civil War service as a Union cavalryman in Company F of the Sixth Cavalry from 1861 to 1864. Topics include camp life; military engagements in Maryland, Virginia, and Pennsylvania; and Davis's incarceration in the Confederate prison on Belle Isle in the James River at Richmond, Va.
Union cavalryman.
Collection material in English.
Keywords: United States. -- Army -- Military life; United States. -- Army. -- Cavalry, 6th.; Belle Isle (Prison); Prisoners of war -- Virginia -- Richmond; Maryland -- History -- Civil War, 1861-1865 -- Campaigns; Pennsylvania -- History -- Civil War, 1861-1865 -- Campaigns; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Soldiers